2011
DOI: 10.1097/fpc.0b013e328347473a
|View full text |Cite
|
Sign up to set email alerts
|

Association between DRD2/ANKK1 Taq1A genotypes, depression and smoking cessation with nicotine replacement therapy

Abstract: Those having a Taq1A variant allele and a history of depression are likely to experience particular difficulty when trying to stop smoking and may require treatment other than standard doses of nicotine replacement. This finding might explain previous conflicting results for Taq1A and smoking cessation in studies where depression history was not measured, and may help to explain the underlying link between depression and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Observed abstinence effect sizes for the most widely studied of these polymorphisms (rs1800497) suggested that NRT was more effective among persons with the A1/A1 or A1/A2 alleles and bupropion was more effective among persons with the A2/ A2 allele. These results are consistent with more recent trials that have also shown that persons with A1/A1 or A1/A2 genotypes have more favorable response to NRT patch (Breitling et al, 2011;Stapleton, Sutherland, O'Gara, Spirling, & Ball, 2011). Others have suggested a gene (ANKK1) × sex interaction (E. C. Yudkin et al, 2003) or gene (ANKK1) × gene (CYP2B6 or SLC6A3) interactions Lerman et al, 2003;Swan et al, 2007), but the limited state of the science in 2006 precluded these details from informing the design of the current pilot trial, which is aimed at understanding the psychological and behavioral impact of the GF as opposed to the efficacy of the genetically tailored treatment.…”
Section: Introductionsupporting
confidence: 92%
“…Observed abstinence effect sizes for the most widely studied of these polymorphisms (rs1800497) suggested that NRT was more effective among persons with the A1/A1 or A1/A2 alleles and bupropion was more effective among persons with the A2/ A2 allele. These results are consistent with more recent trials that have also shown that persons with A1/A1 or A1/A2 genotypes have more favorable response to NRT patch (Breitling et al, 2011;Stapleton, Sutherland, O'Gara, Spirling, & Ball, 2011). Others have suggested a gene (ANKK1) × sex interaction (E. C. Yudkin et al, 2003) or gene (ANKK1) × gene (CYP2B6 or SLC6A3) interactions Lerman et al, 2003;Swan et al, 2007), but the limited state of the science in 2006 precluded these details from informing the design of the current pilot trial, which is aimed at understanding the psychological and behavioral impact of the GF as opposed to the efficacy of the genetically tailored treatment.…”
Section: Introductionsupporting
confidence: 92%
“…At the level of psychopathology, such comorbid relationships are more the rule than the exception, and may have more functional than etiological significance. Both behavioral and molecular genetic studies support the likelihood, however, that smoking/nicotine dependence and depression share at least some etiological features, including common genetic variance (e.g., Kendler et al 1993;Lyons et al 2008;McCaffery et al 2008) and, possibly, genes/genetic mechanisms (e.g., AudrainMcGovern et al 2004;Pergadia et al 2011;Stapleton et al 2011). While the nature of the genetic overlap is unclear at this point, it suggests that smoking-depression comorbidities are less likely to reflect superficial associations than they are to reflect meaningful 'proxies' for underlying common neurobiological endophenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Positive findings in both association (e.g., Audrain-McGovern et al 2004: Ishii et al 2011Stapleton et al 2011) and genetic linkage (Pergadia et al 2011) studies, however, are providing a promising foundation for future investigations.…”
Section: Molecular Genetics Of Smoking and Depressionmentioning
confidence: 99%
“…Munafo et al (2009) later failed to replicate these findings in a larger cohort. Similar prospective trials have also failed to find a significant mediating effect of the Taq1A genotype on the efficacy of NRT in smoking cessation (Berlin et al, 2005; De Ruyck et al, 2010; Stapleton et al, 2011). …”
Section: Pharmacogenetics Of Drug Effects and Treatment Outcomementioning
confidence: 95%